Cell Death Mechanisms at the Maternal-Fetal Interface: Insights into the Role of Granulysin - Danijela Veljkovic Vujaklija; Sonja Sucic; Tamara Gulic; Marin Dominovic; Daniel Rukavina (Clinical and Developmental Immunology)
During mammal pregnancy, a sensitive balance between hormones, cytokines, humoral factors, and local cellular interactions must be established. Cytotoxic cells infiltrating the decidua are heavily equipped with cytolytic molecules, in particular perforin and granulysin. Granulysin is especially abundant in NK cells which are able to spontaneously secrete high quantities of granulysin. Besides being a potent bactericidal and tumoricidal molecule, granulysin is also found to be a chemoattractant and a proinflammatory molecule. The precise role(s) of granulysin at the maternal-fetal interface has not been elucidated yet. It is possible that it behaves as a double-edged sword simultaneously acting as an immunomodulatory and a host defense molecule protecting both the mother and the fetus from a wide spectrum of pathogens, and on the other hand, in case of an NK cell activation, acting as an effector molecule causing the apoptosis of semiallograft trophoblast cells and consequently leading to various pregnancy disorders or pregnancy loss.